The Development of Service Quality in Blood Glucose Testing for Diabetic Patients by Blood Glucose Meter (BGM), Kho Wang Hospital - sudawannasak, yutthaphong (Health Science Journal of Nakhon Ratchasima College, 2025)
This research aimed to enhance the quality of blood glucose testing services and optimize the quality control process for portable blood glucose meters (BGM) used at point-of-care service units for diabetic patients. The 80 follow-up diabetic patients at Kho Wang Hospital were included in the study. Data were collected using a structured questionnaire, which was divided into four sections: demographic information, awareness, blood glucose testing by BGM, and service quality. Descriptive statistics including frequency, percentage, mean, and standard deviation were conducted for data analysis. The relationships between factors influencing blood glucose control and service quality were analyzed using Chi-square test and Pearson’s Correlation Coefficient. The results indicated that 55.56 of participants were male and the mean age of the patients was 59.40 years. The most common comorbidity was hypertension (47.50%) and 58.75% of patients had been living with diabetes for more than 10 years. Most patients (96.25%) had family members as their primary caregivers. Additionally, 91.25% had demonstrated a high level of awareness regarding blood glucose testing, and 82.50% successfully maintained their blood glucose control. The quality of blood glucose testing services was rated as high, accounting for 91.25%. The analysis of associations demonstrated that comorbidities were correlated with blood glucose control (p-value < 0.05). Furthermore, age (r = 0.71) was positively correlated with the quality of blood glucose testing services (p-value< 0.05). Therefore, enhancing care for diabetic patients, particularly those with comorbidities and the elderly, was essential for improving the quality of blood glucose testing services.